The Construction of Meaning in Robert Frost’s Poem “Fire and Ice” - ., Hendra (ENGLISH JOURNAL, 2016)
Reading is actually a process that involves communication. Particularly when reading a literary text such as poem, readers might go in through similar process, as the other readers subconsciously experience, to construct meaning, so that they will arrive in their interpretation about the poem being read. A poem writtern by Robert Lee Frost entitled “Fire and Ice” has been chosen to be the object of the research and three people coming from different background was appointed purposively to be the participants of the research. They were asked to make their own interpretation about the poem. Their activities when reading the poem itself were observed as well and finally thew were interviewed. It is then found that they could only deal with the stages of coherence and background knowledge.